Distúrbios neurológicos em trabalhadores com baixos níveis de chumbo no sangue. II-Disfunc̈ões neurocomportamentais - Cordeiro, Ricardo [UNESP]; Lima Filho, Euclydes C.; Salgado, Paulo E. T.; Santos, Cleide Oliveira; Constantino, Léa; Salerno Malatesta, Maria Luiza Leão (FapUNIFESP (SciELO), 1996)
This is a cross-sectional study with a randomized choice of individuals aiming at studying the validity of the Brazilian biological exposure limits applied to lead level in the blood (PbB) and delta-aminolevulinic acid in the urine (ALAU), which are 60 μ/dl and 10 mg/g.creat., respectively. Thus, twenty workers, whose PbB and ALAU values have been below these limits over the past two years, were selected at random at a battery plant in the State of S. Paulo, Brazil. The workers were submitted to a variation of the WHO Neurobehavioral Core Test Battery. The results were compared with those obtained for workers of a control group also chosen at random. The lead workers showed memory, mood and motor coordination disorders. Comparing these results with those obtained from the control group, a significant difference was observed (p-value < 0.02). The results indicate that the Brazilian biological exposure limits above should be reconsidered.
Neurological disturbances in workers with low levels of lead in the blood. II-Neuropsychological disorders
Keywords: Higher nervous activity; Lead poisoning, prevention and control; Neurologic manifestations; Occupational exposure, standards; lead; blood; cross-sectional study; human; mental disease; neurologic disease; occupational exposure; Cross-Sectional Studies; Humans; Lead; Mental Disorders; Nervous System Diseases; Occupational Exposure